Use and functions of quotations in scientific discourse – structure of a sample lesson - Vassileva, Irena (Yearbook of the Department of Foreign Languages and Cultures, 2024)
The aim of this article is to present the structure of a sample lesson designed to explain the use of quotations in academic discourse, with a particular focus on their communicative function and evaluation. The need for such a lesson arises from the difficulties frequently observed among students when they have to refer to sources in written assignments. The focus is not on the form of quotations, but on their purpose and justification. The lesson has been successfully conducted for students at two German universities in German and at several British universities in an English version. It can help to further develop students’ awareness of the role, function and significance of quotations in academic discourse, thereby improving their writing skills.